Answer:
Step-by-step explanation:
Identify the slope, m. calculate slope between two known points of the line using the slope formula.
Find the y-intercept. substituting the slope and the coordinates of a point (x, y) on the line in the slope-intercept formula and then solve for b.
Put the equation in standard linear form.
![x'(t) + \dfrac{x(t)}{t + 5} = 5e^{5t}](https://tex.z-dn.net/?f=x%27%28t%29%20%2B%20%5Cdfrac%7Bx%28t%29%7D%7Bt%20%2B%205%7D%20%3D%205e%5E%7B5t%7D)
Find the integrating factor.
![\mu = \exp\left(\displaystyle \int \frac{dt}{t+5}\right) = e^{\ln|t+5|} = t+5](https://tex.z-dn.net/?f=%5Cmu%20%3D%20%5Cexp%5Cleft%28%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bdt%7D%7Bt%2B5%7D%5Cright%29%20%3D%20e%5E%7B%5Cln%7Ct%2B5%7C%7D%20%3D%20t%2B5)
Multiply both sides by
.
![(t+5) x'(t) + x(t) = 5(t+5)e^{5t}](https://tex.z-dn.net/?f=%28t%2B5%29%20x%27%28t%29%20%2B%20x%28t%29%20%3D%205%28t%2B5%29e%5E%7B5t%7D)
Now the left side the derivative of a product,
![\bigg((t+5) x(t)\bigg)' = 5(t+5)e^{5t}](https://tex.z-dn.net/?f=%5Cbigg%28%28t%2B5%29%20x%28t%29%5Cbigg%29%27%20%3D%205%28t%2B5%29e%5E%7B5t%7D)
Integrate both sides.
![(t+5) x(t) = \displaystyle 5 \int (t+5) e^{5t} \, dt](https://tex.z-dn.net/?f=%28t%2B5%29%20x%28t%29%20%3D%20%5Cdisplaystyle%205%20%5Cint%20%28t%2B5%29%20e%5E%7B5t%7D%20%5C%2C%20dt)
On the right side, integrate by parts.
![(t+5) x(t) = \dfrac15 (5t+24) e^{5t} + C](https://tex.z-dn.net/?f=%28t%2B5%29%20x%28t%29%20%3D%20%5Cdfrac15%20%285t%2B24%29%20e%5E%7B5t%7D%20%2B%20C)
Solve for
.
![\boxed{x(t) = \dfrac{5t+24}{5t+25} e^{5t} + \dfrac C{t+5}}](https://tex.z-dn.net/?f=%5Cboxed%7Bx%28t%29%20%3D%20%5Cdfrac%7B5t%2B24%7D%7B5t%2B25%7D%20e%5E%7B5t%7D%20%2B%20%5Cdfrac%20C%7Bt%2B5%7D%7D)
The sum of the left side of these two equations is equal to the same of the right side is these two equations
4x+8y + (-4x+2y) = 20 + 30
10y =50 ( x is eliminated)
y=5
Take this into the second equation
-4x +2y = 30
-4x + 2*5 = 30
x=-5
So x=-5
y=5
Answer:
<em>The options are not visible enough (See Explanation)</em>
Step-by-step explanation:
Given
x:- 1 || 2 || 3 || 4 || 5
y:- 13 || 22 || 37 || 58 || 85
Required
Determine if the function is quadratic
Calculate the difference between the values of y
![Difference = 22 - 13 = 9](https://tex.z-dn.net/?f=Difference%20%3D%2022%20-%2013%20%3D%209)
![Difference = 37 - 22 = 15](https://tex.z-dn.net/?f=Difference%20%3D%2037%20-%2022%20%3D%2015)
![Difference = 58 - 37 = 21](https://tex.z-dn.net/?f=Difference%20%3D%2058%20-%2037%20%3D%2021)
![Difference = 85 - 58 = 27](https://tex.z-dn.net/?f=Difference%20%3D%2085%20-%2058%20%3D%2027)
<em>The resulting difference are: 9 || 15 || 21 || 27</em>
Next; Calculate the difference between the difference of values of y
![Difference = 15 - 9 = 6](https://tex.z-dn.net/?f=Difference%20%3D%2015%20-%209%20%3D%206)
![Difference = 21 - 15 = 6](https://tex.z-dn.net/?f=Difference%20%3D%2021%20-%2015%20%3D%206)
![Difference = 27 - 21 = 6](https://tex.z-dn.net/?f=Difference%20%3D%2027%20-%2021%20%3D%206)
<em>The resulting difference are: 6 || 6 || 6</em>
<em>For the function to be quadratic, the above difference must be the same and since they are the same (6), then the function represents a quadratic function.</em>